Influence of Different Number of Boring on Water Quality and Growth Rate of Galah Shrimp (Macrobrachium rosenbergii) in Recirculation Systems - Sari, Putri Kembar; Pamukas, Niken Ayu; Masjudi, Heri (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2025)
This study was conducted for 50 days in April-May 2024. The rearing of king prawns was carried out in the Laboratory of Aquaculture Technology, Department of Aquaculture, Faculty of Fisheries and Marine Sciences, Riau University. The purpose of this study was to determine the effect of different amounts of bioring on water quality and growth rate of king prawns (Macrobrachium rosenbergii) in the recirculation system. The method used in this research is the experimental method of Completely Randomized Design (CRD), which uses 4 levels of treatment with 3 replications. The treatment applied at this stage of the research is the difference in the number of bioring as follows P0= control, P1= 30 bioring pieces,P2= 60 bioring pieces,P3= 90 bioring pieces. The best treatment was obtained from the treatment with 90 pieces of bioring which produced an absolute weight growth value of 2.20 g, absolute length growth of 4.33 cm, specific growth rate of 5.50%, THC of 20,669 106 cells/ml and survival rate of 93.33%. Water quality parameters measured during the study obtained a temperature of 26.5-29.9°C, pH 7.1-7.9, dissolved oxygen 5.2-6.9 mg/L, ammonia 0.033-0.288 mg/L and nitrite 0.02 – 0.287 mg/L